Development and pilot testing of a mobile health solution for asthma self-management: Asthma action plan smartphone application pilot study - Christopher J Licskai; Todd W Sands; Madonna Ferrone (Canadian Respiratory Journal)
BACKGROUND: Collaborative self-management is a core recommendation of national asthma guidelines; the written action plan is the knowledge tool that supports this objective. Mobile health technologies have the potential to enhance the effectiveness of the action plan as a knowledge translation tool.